Prenatal Exposure to Mercury and Adverse Birth Outcomes in Rio de Janeiro, Brazil: Rio Birth Cohort Study (PIPA Project) - Vianna, Angelica dos Santos; Camara, Volney de Magalhaes; de Figueiredo, Nataly Damasceno; Rodrigues Froes Asmus, Carmen Ildes (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Mercury (Hg) is a highly toxic environmental pollutant, with studies of its prenatal exposure indicating adverse birth outcomes such as low birth weight, preterm delivery, and micro- cephaly. Therefore, we analyzed prenatal Hg exposure levels and their relationship with birth outcomes in pregnant women living in an urban area in the city of Rio de Janeiro. Subjects and Method: A cross-sectional study nested in the prospective birth cohort (PIPA Project) was conducted at the Federal University of Rio de Janeiro Maternity School from October to November 2017. A total of 117 mother-infant pairs were evaluated. The sampling technique used convenience sampling. The independent variables encompassed maternal and cord blood Hg levels, while the dependent variables were birth weight, birth length, head circumference (neonatal anthropometrics), and Apgar score at 1 and 5 minutes. The Hg levels were analyzed using induc- tively coupled plasma-mass spectrometry, and dependent variable data were obtained through medical records. Multiple regression models were applied using the SPSS. Results: The detection rate of maternal and cord blood was 100%, with medians of 0.76 and 0.91 µg/L, respectively. A strong correlation between maternal and cord blood Hg levels was observed (r= 0.70; p<0.010), as well as an inverse association between cord blood Hg and Apgar score at 1 and 5 minutes (b=−0.47; p<0.010; b=−0.34; p<0.010) after adjusting for covariates. Conclusion: Our study provided preliminary evidence that Hg exposure was associated with a worse Apgar score at 1 and 5 minutes. However, the relevance of this finding requires further evaluations due to its potential clinical implications concerning newborn health. Keywords: Mercury, Maternal exposure, Apgar Score, Anthropometry Correspondence: Angelica dos Santos Vianna. Federal University of Rio de Janeiro (UFRJ). Avenida Horacio Macedo sem numero – Proximo a Prefeitura Universitária da UFRJ. Ilha do Fundao – Cidade Universitária. ZIP Code: 21941-598, Rio de Janeiro, RJ, Brazil. Email address: angelica- @iesc.ufrj.br